Achieving the delicate balance between risks & outcomes in a large-scale IT project – a case study on BCIA's airport security system. Issue 1 (May 2016) - Chong-Leng Goh, Jenson; Yun Zuo, Mei; Pan, Shan L
This teaching case describes the journey undertaken by the Beijing Capital International Airport's IT department in the implementation of various large-scale IT projects during the construction of the Terminal 3 project. The case specifically singled out the Airport Security system in the Terminal 3 project and provided a detailed description on its implementation. Airport security has always been one of the key concerns in all Airport management activities. In recent times, Airport security has become a hot topic especially given the increasing threats posted by terrorists (e.g., 9/11 incident and MH370). The case portrays Mr. Roland Lee, the project manager of the Airport Security system, as the central protagonist confronting the various challenges in balancing the risks and the requirements to keep the project on time, on budget and of high quality.